The Effectiveness of the Use of Direct Method in Improving Students' Speaking Skill : A Quasi-Experimental Study of Tenth Grade Students in One of Vocational High Schools in Bandung - Husein, Imelda Wahyuni (2014)
This study entitled "The Effectiveness of the Use of Direct Mehod in Improving Students' Speaking Skill" is aimed to examine the effectiveness of the use of direct method which is applied on tenth grade of vocational high school in Bandung especially in introducing. The effectiveness of the direct method is to measure whether there is a significant difference between two groups: experimental group (given the treatment of direct method) and control group (not given the treatment of direct method) and questionnaire is conducted to find out students' responses toward the use of direct method. This quantitative research is conducted in two classes of tenth grader (X Ak and X TSM). The data were collected by conducting a role play as speaking test (pre-test and post-test) which aims to measure the effectiveness of the use of direct method and questionnaire as instrument to find out students' responses toward the use of direct method. The findings show that the use of direct method is effective in improving students' speaking skill. It can be seen from the significant value that does not exceed the level of significance (0.000<0.005) and there is significant difference between post-test means for experimental group (65.3) and control group (54.3). The computation of effect size shows "large" effect (0.81) for the use of direct method in one of vocational high school in Bandung. In addition, the result of questionnaire shows that the students give positive responses toward the use of direct method in their classroom. It can be concluded that direct method is effective in improving low achiever students' speaking skill. Therefore, it is suggested that if it is neccesary, the teachers should implement the use of direct method in the classroom. Key Words: Teaching Speaking, The use of Direct Method,